Age‐related changes in and determinants of macular ganglion cell‐inner plexiform layer thickness in normal Chinese adults. (20th October 2017) - Huo, Yan J; Guo, Yan; Li, Lei; Wang, Huai Z; Wang, Ya X; Thomas, Ravi; Wang, Ning L
Abstract: Importance: Consideration of age‐related changes in macular ganglion cell‐inner plexiform layer (mGCIPL) thickness are important for glaucoma progression analysis. Background: To report age‐related changes in and the determinants of high‐definition optical coherence tomography (HD‐OCT) measurements of mGCIPL thickness. Design: Cross‐sectional study. Participants: 326 healthy adults. Methods: All subjects underwent Cirrus HD‐OCT measurements of mGCIPL. One‐way analysis of variance (ANOVA) was used to compare mGCIPL thickness between 7 decades based age groups and macular sectors. Multiple regression analysis determined the association between mGCIPL thickness and age, gender, intraocular pressure (IOP), peripapillary retinal nerve fibre layer thickness (pRNFL) and spherical equivalent. Main Outcome Measures: Change in mGCIPL thickness and determinants of thickness. Results: Mean mGCIPL thickness in 295 subjects was 80.80 ± 6.42 μm. Mean mGCIPL decreased by 0.12 μm (95% CI [confidence interval], 0.09–0.16) with every year of age; 1.61 μm (95% CI, 0.08–2.41) per decade. It showed two steep declines with age, first in the fifth and next in the seventh decade with relative stability between them. mGCIPL thickness was associated with pRNFL thickness (β = 0.30, P < 0.001) and IOP (β = −0.19, P = 0.03) but not with gender (β = −1.09, P = 0.116) or spherical equivalent (β = −0. 24, P = 0.145). Conclusions and Relevance: Mean mGCIPL thickness showed a small age‐related linear decrease with two steep drops in the fifth and seventh decades. Thinner mGCIPL was independently associated with age, thinner pRNFL and higher IOP. These factors should be considered if using mGCIPL to detect progression of glaucoma and other optic neuropathies characterized by the loss of retinal ganglion cells.